Catalogue of Aphidophagous syrphids preying on aphid pests from herbaceous crops and weeds in Spain and Portugal (Bollettino di zoologia agraria e bachicoltura, 2024)
A revision and taxonomic update of the relationships syrphid-aphid from herbaceous plants known in the Iberomacaronesian region, is provided. New data about larva feeding of aphidophagous syrphid species, in herbaceous crops and weeds in Mediterranean areas are also given. The hoverfly species with a wide trophic spectre were Episyrphus balteatus, Eupeodes corollae and Sphaerophoria scripta. On the other hand Epistrophe eligans and Platycheirus scutatus are cited by first time in the Iberian Peninsule preying on aphids from herbaceous plants. A check-list of all Ibero-Macaronesian relatioships syrphids-aphid-plant is included.
Keywords: Syrphidae; Spain; Portugal; herbaceous crops; weeds